Aortic valve replacement in a bicuspid aortic valve patient followed by reoperation for ascending aorta rupture: a case report - Yang, Yuehang; Liu, Xinyi; Liu, Junwei; Shi, Jiawei; Li, Huadong (Frontiers in Cardiovascular Medicine, 2024)
Bicuspid aortic valve (BAV), the most common congenital cardiac anomaly, predisposes individuals to aortic stenosis and regurgitation due to valve degeneration. Abnormal hemodynamics, arterial wall characteristics, and genetic factors contribute to ascending aorta dilatation, potentially leading to severe complications like aortic dissection. Presently, the most recent guidelines propose that individuals with BAV requiring valve replacement due to valve dysfunction should undergo simultaneous replacement of the ascending aorta when the diameter of aortic dilatation exceeds 4.5 cm. A 60-year-old female patient previously underwent mechanical aortic valve replacement and ascending aortoplasty at our center due to aortic stenosis and a 4.3 cm diameter ascending aorta. In the sixth postoperative year, she was readmitted due to ascending aorta rupture, resulting in blood entering the right atrium and causing acute right heart failure. We performed repair of the rupture and concomitant ascending aorta replacement to prevent further exacerbation of the patient's condition.